1102 Relationship Between Emotional Distress And Sleep Duration Among Hispanics Using The 2018 National Health Interview Survey Dataset. (27th May 2020) - Garcia, J; Moore, J; Payano, L; Rogers, A; Poke, P; Casimir, G; Jean-Louis, G; Seixas, A
Abstract: Introduction: Although Hispanics experience a high level of shorter sleep duration (< 7 hrs./24 period), a clear mechanism or cause is lacking. Previous research indicate that emotional distress may explain the burden of shorter sleep among blacks. Applying these findings to Hispanics, we investigated whether emotional distress explains the burden of short sleep duration (< 7 hrs.) among Hispanics and if this relationship varies by sex Methods: We used data from the 2018 National Health Interview Survey (NHIS) dataset, a nationally representative sample, in which only Hispanic ethnicity participants (N=3, 091) were analyzed. Average sleep duration was self-reported and measured in hours. Emotional distress was measured using Kessler 6, which measures how an individual felt over the past 30 days: nervous, hopeless, restless/fidgety, depressed, effortful and worthless. To assess the association between short sleep duration and emotional distress, we performed Pearson correlation, hierarchical regression analyses, and stratified this relationship by sex to determine if this relationship differed between males and females, adjusting for covariates. Results: Of the total sample of 3, 091 Hispanics, 1, 762 were female, and 1, 329 were male. Sleep duration and emotional distress were negatively correlated among females ( r = -.27, p <.001) and males (r=-.18, p <.001). Among Hispanic females, sleep duration significantly predicted emotional distress, β = -.27, t = -11.60, p <.001, and explained a significant portion of variance in emotional distress, R 2 = .07, F = 134.63, p <.001. While, among Hispanic males, sleep significantly predicted emotional distress (β = -.18, t =-6.5, p <.001) and explained a significant portion of the variance in emotional distress ( R 2 = .03, F = 42.37, p <.001). Conclusion: Our findings indicate that a negative sleep-ED relationship, suggesting that shorter sleep was predictive of higher levels of emotional distress among Hispanics and that this relationship is greater among Hispanic females, compared males. Support: K01HL135452, R01MD007716, R01HL142066, and K07AG052685